UNFOLDING THE INDEPENDENCE DILEMMA OF THE INTERNAL SUPERVISION UNIT AUDITORS: PHENOMENOLOGY STUDY - Syarif Syahrir Malle; Alimuddin Alimuddin; Nirwana Nirwana (Universitas Patria Artha, 2019)
This study aimed to comprehend and unfolding the reality of the independence dilemma faced by auditors of the Internal Control Unit at the Alauddin Makassar Islamic University. In achieveing the objective of the study, the reasercher conducted observation and interviews in collecting the data, while the exploration of the understanding and awareness of the informant is done in depth using epoche. Data were analyzed by qualitative method interpretively with phenomenology as a research design. The results of the study revealed that the reality experienced by the auditors of SPI UIN Alauddin Makassar showed an ethical gap. There was a